Geoffrey Francis Hattersley-Smith ('Geoff'). (7th March 2013) - Stonehouse, Bernard
<x content-type="archive" xml:space="preserve">Abstract</x> Geoffrey Francis Hattersley-Smith ('Geoff'), who died on 21 July 2012, served for many years as a polar field scientist, contributing substantially to glaciological and geological surveys in both north and south polar regions. In later life he undertook research in another discipline altogether – the sorting and cataloguing of polar place names – an achievement in scholarship for which all other polar researchers may be thankful.